Azo‐Initiator‐Induced Cascade Defect Passivation for Efficient and Stable Planar Perovskite Solar Cells. Issue 8 (12th May 2022) - Li, Mingguang; Gao, Huan; Peng, Ying; Tang, Senlin; Liu, Ying; Deng, Yong; Xu, Ligang; Chen, Runfeng
Abstract : Remarkable progress in perovskite solar cells (PSCs) has been made by virtue of surface and bulk modification for defect control of perovskite layers, however, the interior defects in the perovskite layer can be hardly passivated by means of conventional passivation strategies, which makes perovskites prone to decomposition with inferior device performance. Here, the authors propose a cascade defect passivation strategy to doubly reduce perovskite defects by introducing a series of azo radical initiators. The primary passivation process of the azo compounds is realized on the perovskite surfaces through strong coordination interactions between Pb 2+ and carbonyl/cyano groups. The secondary passivation occurs after thermal treatment, and the decomposed products diffuse into the interior defects of the initial passivated perovskite films through grain boundaries to accomplish the cascade defect passivation. Excitingly, this passivation strategy inhibits unwanted defect‐assisted recombination effectively, and thus CH3 NH3 PbI3 (MAPbI3 )‐based inverted PSCs exhibit a significant increase in power conversion efficiency (PCE) from 16.92% to 19.69%. Moreover, the dual‐passivated PSCs show only 10% PCE loss after 3000 h in an inert atmosphere. Overall, the first proposed cascade defect passivation strategy is highly efficient in promoting defect healing of perovskites, demonstrating a new way to prepare high‐quality perovskite films for high‐performance PSCs. Abstract : A cascade defect passivation strategy is proposed to doubly reduce perovskite defects by introducing free radical azo‐initiators. Both the surface and the interior perovskite defects can be healed efficiently and thus the modified CH3 NH3 PbI3 (MAPbI3 )‐based inverted perovskite solar cells (PSCs) exhibit significantly enhanced efficiency with the power conversion efficiency (PCE) approaching 20% as well as high long‐term stability.